2012
DOI: 10.1029/2012jd017716
|View full text |Cite
|
Sign up to set email alerts
|

Variabilities in ozone at a semi‐urban site in the Indo‐Gangetic Plain region: Association with the meteorology and regional processes

Abstract: The Indo‐Gangetic Plain (IGP) region is one of the most densely populated regions in the World, but ground‐based observations of air pollutants are highly limited in this region. Here, surface ozone observations made during March 2009–June 2011 at a semi‐urban site (Pantnagar; 29.0°N, 79.5°E, 231 m amsl) in the IGP region are presented. Ozone mixing ratios show a daytime photochemical buildup with ozone levels sometimes as high as 100 ppbv. Seasonal variation in 24‐h average ozone shows a distinct spring maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
82
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 94 publications
6
82
0
Order By: Relevance
“…The accuracy of these measurements is reported to be about 5 % (Kleinmann et al, 1994). The response time of such instruments is about 20 s and instruments have a lower detection limit of 1 ppbv (Ojha et al, 2012). Here, we have used the hourly and monthly average data for the model evaluation.…”
Section: Observational Datasetmentioning
confidence: 99%
See 3 more Smart Citations
“…The accuracy of these measurements is reported to be about 5 % (Kleinmann et al, 1994). The response time of such instruments is about 20 s and instruments have a lower detection limit of 1 ppbv (Ojha et al, 2012). Here, we have used the hourly and monthly average data for the model evaluation.…”
Section: Observational Datasetmentioning
confidence: 99%
“…It was shown that the anthropogenic emissions and their subsequent photochemical degradation over south Asia influence air quality over the Himalayas (e.g. Ojha et al, 2012;Sarangi et al, 2014) and the Tibetan Plateau (Lüthi et al, 2015) as well as the marine environment downwind of India (e.g. Lawrence and Lelieveld, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A correlation analysis between ozone levels over a site in the IGP region and Nainital along with the mixing depth data suggests that emissions and photochemical processes in the IGP region influence the air quality of pristine Himalayan region, particularly during midday hours of spring. Ozone seasonality over the IGP region is different than that over southern India (Ojha et al, 2012).…”
Section: Science At High-altitude Sites Of Aries -Astrophysics and Atmentioning
confidence: 99%